A positive electrode host material for lithium-sulfur battery based on manganese sulfide-molybdenum disulfide heterojunction and its preparation method and application
Through the use of manganese sulfide-molybdenum disulfide heterobond composite materials, the problems of low utilization rate of active sulfur and low catalytic efficiency in lithium sulfur batteries are solved, and lithium sulfur batteries with high capacity and long cycle life are realized. By hydrothermal method, a lithium sulfur battery is used to achieve a high capacity and long cycle life. Prepare two-dimensional nanosheet structures and regulate the electronic effects of the interface, improving the electron conductivity and catalytic properties.
Patent Information
- Application Number
- CN202211155266.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-09-22
- Publication Date
- 2025-01-17
- Estimated Expiration
- 2042-09-22
AI Technical Summary
The low utilization rate of active sulfur in lithium-sulfur batteries leads to low discharge capacity and poor intrinsic electronic conductivity of transition metal sulfides, resulting in low catalytic efficiency and the inability to achieve stable circulation in extreme environments of high load/low liquid sulfur ratio.
Manganese sulfide-molybdenum disulfide heterojunction composite material was used to prepare two-dimensional nanosheet structures by hydrothermal method to regulate the interface electronic effects, improve the electronic conductivity, and accelerate the discharge reaction kinetics through the efficient catalytic performance of MoS2 to reduce sulfurization Lithium nucleation free energy.
Lithium sulfur battery with high capacity, high Coulomb efficiency and long cycle life has been achieved. The discharge capacity of the first circle reaches 1388mAh g-1, and it remains 1110mAh g-1 after 300 cycles, which significantly improves the utilization rate of active sulfur and battery stability. .
Smart Images

Figure CN115621435B_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of lithium-sulfur batteries, and in particular to a positive electrode host material for lithium-sulfur batteries based on a manganese sulfide-molybdenum disulfide heterojunction, and a preparation method and application thereof. Background Art
[0002] Lithium-sulfur batteries have a very high theoretical specific capacity of 1672 mAh g -1 , High mass specific energy density: 2500Wh Kg -1 , and the raw material sulfur is abundant in the earth's crust, low in price, and environmentally friendly, so it is regarded as one of the most promising high-energy storage devices. However, there are still many key issues in lithium-sulfur batteries that slow down their commercialization process, such as sulfur (5×10 -30 S cm -1 ) and the low intrinsic electronic conductivity of the discharge end product lithium sulfide, which leads to a serious reduction in the utilization rate of active sulfur, especially for high sulfur loading conditions, making the discharge capacity of lithium-sulfur batteries extremely low. At the same time, the charging and discharging mechanism of lithium-sulfur batteries mainly involves sulfur (S8), soluble lithium polysulfide (Li2S n , 4≤n≤8) and solid lithium sulfide (Li2S2 / Li2S). During the electrochemical redox process, the generated high-order polysulfides are easily soluble in ether electrolytes. Affected by the electric field strength and concentration gradient, the intermediate polysulfide species undergo a serious shuttle effect between the positive and negative electrodes, resulting in severe capacity decay and loss of active sulfur. In addition, the conversion process of polysulfides involves a "solid-liquid-solid" multiphase conversion reaction, which often leads to slow redox reaction kinetics due to the high reaction energy barrier, exacerbating the occurrence of the shuttle effect and increasing the degree of polarization.
[0003] Nowadays, polar materials such as transition metal oxides, sulfides, and nitrides have been proven to have strong adsorption capacity for polysulfides and are widely used in lithium-sulfur batteries. Among them, transition metal sulfides have strong chemical adsorption capacity for polysulfur intermediates due to their unique structure and surface properties, and can significantly improve the redox kinetics of polysulfides. So far, a variety of transition metal sulfides (MoS2, Co3S4, FeS2, SnS, etc.) have been reported for use as positive electrode host materials for lithium-sulfur batteries. However, due to the poor intrinsic electronic conductivity of transition metal sulfides, the adsorbed polysulfides are difficult to convert quickly, covering the active sites and reducing the catalytic efficiency, which ultimately causes the lithium-sulfur battery to have fast capacity decay, active sulfur loss and low coulombic efficiency, and cannot achieve many problems such as stable cycling of lithium-sulfur batteries in extreme battery environments with high loading / low liquid sulfur ratio. Summary of the invention
[0004] The present application is made in view of the above-mentioned problems, and its purpose is to provide a lithium-sulfur battery positive electrode host material with good intrinsic electronic conductivity, strong adsorption capacity for polysulfides and high catalytic activity, so as to achieve high capacity, high coulombic efficiency and long cycle life of lithium-sulfur batteries.
[0005] In order to achieve the above-mentioned purpose, the present application provides an effective means. Provided is a manganese sulfide-molybdenum disulfide heterojunction lithium-sulfur battery positive electrode host material and its preparation method and application. The heterojunction composite material prepared by the method has a two-dimensional nanosheet structure, which is conducive to exposing more active sites and promoting electrolyte infiltration; the intrinsic electronic conductivity of the material is improved by regulating the interface electronic effect through manganese-sulfur-molybdenum bond bridging, thereby improving the utilization rate of active sulfur; due to the inherent semiconductor properties of the two transition metal sulfides, the built-in electric field spontaneously formed at the pn junction makes the electronegative polysulfide tend to migrate from p-type to n-type, alleviating the shuttle effect caused by the diffusion of polysulfide into the electrolyte due to the concentration gradient. At the same time, thanks to the efficient catalytic performance of MoS2, the nucleation free energy of lithium sulfide can be reduced, the reaction kinetics of the discharge process can be accelerated, thereby improving the capacity, coulombic efficiency and cycle life of the lithium-sulfur battery. The preparation method of manganese sulfide-molybdenum disulfide heterojunction sulfur-based positive electrode host material has a simple process, low cost and easy large-scale production.
[0006] The first aspect of the present application provides a design concept for a manganese sulfide-molybdenum disulfide heterojunction lithium-sulfur battery positive electrode host material, with molybdenum disulfide nanosheets as the main body, and manganese sulfide nanoparticles anchored on the molybdenum disulfide nanosheets to form a composite material with a manganese sulfide-molybdenum disulfide heterostructure.
[0007] The second aspect of the present application provides a method for preparing a positive electrode host material for a manganese sulfide-molybdenum disulfide heterojunction lithium-sulfur battery, the steps of which include:
[0008] (1) Dissolve 0.1 g of manganese disulfide tetrahydrate and 0.206 g of anhydrous sodium molybdate in 50 mL to 80 mL of ultrapure water, and stir in a 30°C water bath for 1 h to obtain a suspension containing manganese molybdate. Then add 0.412 g of thioacetamide, and continue stirring at room temperature for 1 h.
[0009] (2) The obtained mixed solution was transferred to a 100 mL polytetrafluoroethylene hydrothermal reactor, and the temperature was raised to 180-240° C. in a forced air oven and kept at this temperature for 8-24 h.
[0010] (3) After the reactor is cooled naturally, the product is washed with ultrapure water and ethanol alternately for 4 times, and then the washed sample is placed in a vacuum oven and dried at 60° C. for 12 h to obtain a sample of manganese sulfide-molybdenum disulfide.
[0011] (4) Grinding manganese sulfide-molybdenum disulfide powder and sublimated sulfur powder to fully mix them in a weight ratio of 3:7-1:9, then transferring them to a glass bottle and sealing them with an inert gas, melting them in an oven at 155°C for 15 hours, and cooling them naturally to obtain a sulfur / manganese sulfide-molybdenum disulfide heterojunction lithium-sulfur battery positive electrode material.
[0012] The volume of the ultrapure water solvent in step (1) is 50 mL or 80 mL.
[0013] The temperature and time in step (2) are 220° C., 20 h or 240° C., 24 h, respectively.
[0014] In step (4), the weight ratio of the host material of the manganese sulfide-molybdenum disulfide powder and the sublimated sulfur powder to sulfur is 3:7 or 1:9.
[0015] The parameters and conditions of each step are as follows: (1) The volume of solvent (deionized water) used in the solvothermal method is 50 mL or 80 mL; (2) The holding time and temperature are 220℃ for 20 h or 240℃ for 24 h; (3) The ratio of host material to sulfur content is 3:7 or 1:9; (4) Button cell test or soft pack cell test is used to evaluate the electrochemical performance. The corresponding reasons are as follows: (1) Affecting the pressure of the reaction process, regulating the morphology and pores of the sample; (2) Regulating the morphology of the sample; (3) The sulfur content affects the electrochemical catalytic effect of the host material; (4) Button cell and soft pack cell have different ways of evaluating the electrochemical performance.
[0016] The setting of the conditions in step (1) affects the pressure of the reaction process and regulates the morphology and pores of the sample; the setting of the conditions in step (2) regulates the morphology of the sample; and the setting of the conditions in step (3) affects the electrochemical catalytic effect of the host material by adjusting the sulfur content.
[0017] The third aspect of the present application also provides an application of a manganese sulfide-molybdenum disulfide heterojunction lithium-sulfur battery positive electrode host material, according to the mass ratio of sulfur / manganese sulfide-molybdenum disulfide: super P:PVDF of 7:2:1 or 8:1:1, sulfur / manganese sulfide-molybdenum disulfide and conductive carbon super P are ground and mixed, and then 5wt% PVDF binder and an appropriate amount of NMP solution are added to form a uniform and fluid slurry (solid content ratio is 30-40%), and the specific amount of NMP used is regulated according to the total mass of the slurry solids and the corresponding solid content ratio, and the solid content ratio corresponding to the slurry adjustment of different materials is slightly different. Finally, the formed uniform and fluid slurry is placed on aluminum foil, scraped with a scraper to form a uniform coating, dried at 60°C in a vacuum drying oven for 24 hours, cut into discs, weighed, and then assembled into button batteries.
[0018] An application of a manganese sulfide-molybdenum disulfide heterojunction lithium-sulfur battery positive electrode host material, in a dry room, a soft pack battery is assembled by stacking, and the area of the coated sulfur / manganese sulfide-molybdenum disulfide working electrode is about 24.1cm 2 (43×56mm), the lithium foil area is about 26.1cm 2 (45×58mm), and seal the aluminum-plastic film using a vacuum packaging machine.
[0019] The electrochemical performance of button cells and soft-pack batteries is evaluated differently.
[0020] Beneficial effects of the present invention:
[0021] 1) The present invention adds tetrahydrated manganese disulfide, anhydrous sodium molybdate and thioacetamide to ultrapure water, stirs at room temperature, and reacts by hydrothermal method to obtain a composite material having a manganese sulfide-molybdenum disulfide heterostructure. The present invention has a short preparation process and a simple process, and the experimental repeatability is good. The prepared manganese sulfide-molybdenum disulfide heterojunction composite material has high electronic conductivity, high catalytic activity for polysulfur intermediate species, and strong chemical adsorption for polysulfides, which effectively alleviates the shuttle effect and improves the kinetics of the electrode reaction process.
[0022] 2) The prepared sulfur / manganese sulfide-molybdenum disulfide heterogeneous sulfur-based cathode has a current of 0.5C (1C = 1675mA g -1 ), the first cycle discharge capacity is up to 1388mAh g -1 After 300 cycles, the reversible discharge capacity is 1110 mAh g -1 , showing excellent long-cycle stability and high battery capacity. At the same time, the sulfur surface loading was increased to 14.7 mg cm -2 After 100 cycles, it can still maintain 9.9 mAh cm -2 The discharge surface capacity has great potential for application as a commercial lithium-sulfur battery electrode material.
[0023] 3) The present invention is a hydrothermal method with a short process and simple technology to prepare a manganese sulfide-molybdenum disulfide heterojunction sulfur positive electrode host material with high electronic conductivity, strong polarity and efficient catalytic conversion of polysulfides. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 X-ray diffraction spectra of manganese sulfide-molybdenum disulfide heterojunction composite material, molybdenum sulfide and manganese sulfide samples;
[0025] Figure 2 Raman spectra of manganese sulfide-molybdenum disulfide heterojunction composites, molybdenum sulfide and manganese sulfide samples;
[0026] Figure 3is the nitrogen adsorption-desorption curve of manganese sulfide-molybdenum disulfide heterojunction composite material;
[0027] Figure 4 This is a field emission scanning electron microscope image of a manganese sulfide-molybdenum disulfide heterojunction composite material;
[0028] Figure 5 This is a transmission electron microscope image of a manganese sulfide-molybdenum disulfide heterojunction composite material;
[0029] Figure 6 The cyclic voltammetry curve of sulfur / manganese sulfide-molybdenum disulfide heterojunction composite sulfur-based electrode;
[0030] Figure 7 This is the long cycle curve of sulfur / manganese sulfide-molybdenum disulfide heterojunction composite sulfur-based electrode at 0.5C rate;
[0031] Figure 8 This is the long cycle curve of sulfur / manganese sulfide-molybdenum disulfide heterojunction composite sulfur-based electrode at 2C rate;
[0032] Fig. 9 Long cycle curves of sulfur / manganese sulfide-molybdenum disulfide heterojunction composite sulfur-based electrodes with different sulfur loadings at 0.2C rate and low liquid / sulfur ratio;
[0033] Fig.10 This is the long cycle curve of sulfur / manganese sulfide-molybdenum disulfide heterojunction composite sulfur-based soft-pack battery at 0.05C rate. DETAILED DESCRIPTION
[0034] Below, the preparation method and application implementation method of the positive electrode host material of the present application are specifically disclosed with appropriate reference to the accompanying drawings. However, there may be cases where unnecessary detailed descriptions are omitted. For example, there are cases where detailed descriptions of well-known matters and repeated descriptions of actually the same structure are omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate the understanding of those skilled in the art. In addition, the drawings and the following descriptions are provided for those skilled in the art to fully understand the present application and are not intended to limit the subject matter described in the claims.
[0035] "Scope" disclosed in the present application is limited in the form of lower limit and upper limit, and a given range is limited by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundary of a special range. The scope limited in this way can be including end values or not including end values, and can be arbitrarily combined, that is, any lower limit can be combined with any upper limit to form a scope. For example, if the scope of 60-120 and 80-110 is listed for a specific parameter, it is understood that the scope of 60-110 and 80-120 is also expected. In addition, if the minimum range values 1 and 2 are listed, and if the maximum range values 3, 4 and 5 are listed, the following scope can be all expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5. In the present application, unless otherwise specified, the numerical range "ab" represents the abbreviation of any real number combination between a and b, wherein a and b are real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" have been listed in this article, and "0-5" is just an abbreviation of these numerical combinations.
[0036] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.
[0037] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.
[0038] If there is no special explanation, all steps of the present application can be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may further include step (c), which means that step (c) may be added to the method in any order. For example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.
[0039] If there is no special explanation, the "include" and "comprising" mentioned in this application are open-ended or closed-ended. For example, the "include" and "comprising" may mean that other components not listed may also be included or only the listed components may be included or only the listed components may be included.
[0040] If not specifically stated, in this application, the term "or" is inclusive. For example, the phrase "A or B" means "A, B, or both A and B". More specifically, any of the following conditions satisfies the condition "A or B": A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).
[0041] Hereinafter, the embodiments of the present application will be described. The embodiments described below are exemplary and are only used to explain the present application, and should not be construed as limiting the present application. If no specific techniques or conditions are indicated in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. If the manufacturer is not indicated in the reagents or instruments used, they are all conventional products that can be obtained commercially.
[0042] Example 1
[0043] (1) 0.1 g of manganese disulfide tetrahydrate and 0.206 g of anhydrous sodium molybdate were dissolved in 50 mL of ultrapure water and stirred in a water bath at 30° C. for 2 h to obtain a suspension containing manganese tetrathiomolybdate. Subsequently, 0.412 g of thioacetamide was added and the mixture was stirred at room temperature for 3 h.
[0044] (2) The obtained mixed solution was transferred to a 100 mL polytetrafluoroethylene hydrothermal reactor, heated to 220° C. in a forced air oven, and kept warm for 20 h.
[0045] (3) After the reactor is cooled naturally, the product is washed with ultrapure water and ethanol alternately for 4 times, and then the washed sample is placed in a vacuum oven and dried at 60° C. for 12 h to obtain a sample of manganese sulfide-molybdenum disulfide.
[0046] (4) Grind the manganese sulfide-molybdenum disulfide powder and the sublimated sulfur powder to make them fully mixed in a ratio of 3:7, then transfer them into a glass bottle and seal it with an inert gas, melt react in an oven at 155°C for 15 hours, and cool naturally to obtain a sulfur / manganese sulfide-molybdenum disulfide heterojunction lithium-sulfur battery positive electrode material.
[0047] (5) Sulfur / manganese sulfide-molybdenum disulfide and conductive carbon super P were ground and mixed, and then 5wt% PVDF binder and an appropriate amount of NMP solution were added to form a uniform and fluid slurry. The mass ratio of sulfur / manganese sulfide-molybdenum disulfide: super P:PVDF was 7:2:1. Finally, the formed uniform and fluid slurry was placed on aluminum foil and scraped with a scraper to form a uniform coating. The coating was dried in a vacuum drying oven at 60°C for 24h, cut into discs, weighed, and then assembled into button batteries.
[0048] Example 2
[0049] (1) 0.2 g of manganese disulfide tetrahydrate and 0.412 g of anhydrous sodium molybdate were dissolved in 70 mL of ultrapure water and stirred in a water bath at 30° C. for 2 h to obtain a suspension containing manganese tetrathiomolybdate. Subsequently, 0.412 g of thioacetamide was added and the mixture was stirred at room temperature for 3 h.
[0050] (2) The obtained mixed solution was transferred to a 100 mL polytetrafluoroethylene hydrothermal reactor, heated to 220° C. in a forced air oven, and kept warm for 20 h.
[0051] (3) After the reactor is cooled naturally, the product is washed with ultrapure water and ethanol alternately for 4 times, and then the washed sample is placed in a vacuum oven and dried at 60° C. for 12 h to obtain a sample of manganese sulfide-molybdenum disulfide.
[0052] (4) Grind the manganese sulfide-molybdenum disulfide powder and the sublimated sulfur powder to make them fully mixed in a ratio of 3:7, then transfer them into a glass bottle and seal it with an inert gas, melt react in an oven at 155°C for 15 hours, and cool naturally to obtain sulfur / manganese sulfide-molybdenum disulfide, a positive electrode material for lithium-sulfur batteries.
[0053] (5) Sulfur / manganese sulfide-molybdenum disulfide and conductive carbon super P were ground and mixed, and then 5wt% PVDF binder and an appropriate amount of NMP solution were added to form a uniform and fluid slurry. The mass ratio of sulfur / manganese sulfide-molybdenum disulfide: super P:PVDF was 7:2:1. Finally, the formed uniform and fluid slurry was placed on aluminum foil and scraped with a scraper to form a uniform coating. The coating was dried in a vacuum drying oven at 60°C for 24h, cut into discs, weighed, and then assembled into button batteries.
[0054] Example 3
[0055] (1) 0.1 g of manganese disulfide tetrahydrate and 0.206 g of anhydrous sodium molybdate were dissolved in 70 mL of ultrapure water and stirred in a water bath at 30° C. for 2 h to obtain a suspension containing manganese tetrathiomolybdate. Subsequently, 0.412 g of thioacetamide was added and the mixture was stirred at room temperature for 3 h.
[0056] (2) The obtained mixed solution was transferred to a 100 mL polytetrafluoroethylene hydrothermal reactor, heated to 240° C. in a forced air oven, and kept warm for 24 h.
[0057] (3) After the reactor is cooled naturally, the product is washed with ultrapure water and ethanol alternately for 4 times, and then the washed sample is placed in a vacuum oven and dried at 60° C. for 12 h to obtain a sample of manganese sulfide-molybdenum disulfide.
[0058] (4) Grind the manganese sulfide-molybdenum disulfide powder and the sublimated sulfur powder to make them fully mixed in a ratio of 3:7, then transfer them into a glass bottle and seal it with an inert gas, melt react in an oven at 155°C for 15 hours, and cool naturally to obtain sulfur / manganese sulfide-molybdenum disulfide, a positive electrode material for lithium-sulfur batteries.
[0059] (5) Sulfur / manganese sulfide-molybdenum disulfide and conductive carbon super P were ground and mixed, and then 5wt% PVDF binder and an appropriate amount of NMP solution were added to form a uniform and fluid slurry. The mass ratio of sulfur / manganese sulfide-molybdenum disulfide: super P:PVDF was 7:2:1. Finally, the formed uniform and fluid slurry was placed on aluminum foil and scraped with a scraper to form a uniform coating. The coating was dried in a vacuum drying oven at 60°C for 24h, cut into discs, weighed, and then assembled into button batteries.
[0060] Example 4
[0061] (1) 0.1 g of manganese disulfide tetrahydrate and 0.206 g of anhydrous sodium molybdate were dissolved in 70 mL of ultrapure water and stirred in a water bath at 30° C. for 2 h to obtain a suspension containing manganese tetrathiomolybdate. Subsequently, 0.412 g of thioacetamide was added and the mixture was stirred at room temperature for 3 h.
[0062] (2) The obtained mixed solution was transferred to a 100 mL polytetrafluoroethylene hydrothermal reactor, heated to 220° C. in a forced air oven, and kept warm for 20 h.
[0063] (3) After the reactor is cooled naturally, the product is washed with ultrapure water and ethanol alternately for 4 times, and then the washed sample is placed in a vacuum oven and dried at 60° C. for 12 h to obtain a sample of manganese sulfide-molybdenum disulfide.
[0064] (4) Grind the manganese sulfide-molybdenum disulfide powder and the sublimated sulfur powder to make them fully mixed in a ratio of 1:9, then transfer them into a glass bottle and seal it with an inert gas, melt react in an oven at 155°C for 15 hours, and cool naturally to obtain sulfur / manganese sulfide-molybdenum disulfide, a positive electrode material for lithium-sulfur batteries.
[0065] (5) Sulfur / manganese sulfide-molybdenum disulfide and conductive carbon super P were ground and mixed, and then 5wt% PVDF binder and an appropriate amount of NMP solution were added to form a uniform and fluid slurry. The mass ratio of sulfur / manganese sulfide-molybdenum disulfide: super P:PVDF was 8:1:1. Finally, the formed uniform and fluid slurry was placed on aluminum foil and scraped with a scraper to form a uniform coating. The coating was dried in a vacuum drying oven at 60°C for 24h, cut into discs, weighed, and then assembled into button batteries.
[0066] Example 5
[0067] (1) 0.1 g of manganese disulfide tetrahydrate and 0.206 g of anhydrous sodium molybdate were dissolved in 70 mL of ultrapure water and stirred in a water bath at 30° C. for 2 h to obtain a suspension containing manganese tetrathiomolybdate. Subsequently, 0.412 g of thioacetamide was added and the mixture was stirred at room temperature for 3 h.
[0068] (2) The obtained mixed solution was transferred to a 100 mL polytetrafluoroethylene hydrothermal reactor, heated to 220° C. in a forced air oven, and kept warm for 20 h.
[0069] (3) After the reactor is cooled naturally, the product is washed with ultrapure water and ethanol alternately for 4 times, and then the washed sample is placed in a vacuum oven and dried at 60° C. for 12 h to obtain a sample of manganese sulfide-molybdenum disulfide.
[0070] (4) Grind the manganese sulfide-molybdenum disulfide powder and the sublimated sulfur powder to make them fully mixed in a ratio of 1:9, then transfer them into a glass bottle and seal it with an inert gas, melt react in an oven at 155°C for 15 hours, and cool naturally to obtain sulfur / manganese sulfide-molybdenum disulfide, a positive electrode material for lithium-sulfur batteries.
[0071] (5) Sulfur / manganese sulfide-molybdenum disulfide and conductive carbon super P were ground and mixed, and then 5wt% PVDF binder and an appropriate amount of NMP solution were added to form a uniform and fluid slurry. The mass ratio of sulfur / manganese sulfide-molybdenum disulfide: super P:PVDF was 8:1:1. Finally, the formed uniform and fluid slurry was placed on aluminum foil and scraped with a scraper to form a uniform coating. The coating was dried in a vacuum drying oven at 60°C for 24h, cut into discs, weighed, and then assembled into soft-pack batteries.
[0072] Figure 6-9 The corresponding electrochemical performance of the button battery test. Fig.10 Test the corresponding electrochemical properties for soft pack batteries.
[0073] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are only examples, and the embodiments having the same structure as the technical idea and exerting the same effect within the scope of the technical solution of the present application are all included in the technical scope of the present application. In addition, without departing from the scope of the main purpose of the present application, various modifications that can be thought of by those skilled in the art to the embodiments and other methods of combining some of the constituent elements in the embodiments are also included in the scope of the present application.
Claims
1. A method for preparing a positive electrode host material for a manganese sulfide-molybdenum disulfide heterojunction lithium-sulfur battery, characterized in that: The steps include: (1) Dissolve 0.1 g of manganese disulfide tetrahydrate and 0.206 g of anhydrous sodium molybdate in 50 mL-80 mL of ultrapure water, and stir in a 30°C water bath for 1 h to obtain a suspension containing manganese tetrathiomolybdate; then add 0.412 g of thioacetamide, and continue stirring at room temperature for 1 h; (2) Transfer the obtained mixed solution to a 100 mL polytetrafluoroethylene hydrothermal reactor, heat it to 180-240°C in a forced air oven, and keep it warm for 8-24 hours; (3) After the reactor is cooled naturally, the product is washed with ultrapure water and ethanol alternately for 4 times, and then the washed sample is placed in a vacuum oven and dried at 60°C for 12 hours to obtain a sample of manganese sulfide-molybdenum disulfide; (4) Grind the manganese sulfide-molybdenum disulfide powder and the sublimated sulfur powder to make them fully mixed in a weight ratio of 3:7-1:9, then transfer them into a glass bottle and seal them with an inert gas, melt react in an oven at 155°C for 15 hours, and cool naturally to obtain a sulfur / manganese sulfide-molybdenum disulfide heterojunction lithium-sulfur battery positive electrode material.
2. The method for preparing the positive electrode host material of manganese sulfide-molybdenum disulfide heterojunction lithium-sulfur battery according to claim 1, characterized in that: The volume of the ultrapure water solvent in step (1) is 50 mL or 80 mL.
3. The method for preparing the positive electrode host material of manganese sulfide-molybdenum disulfide heterojunction lithium-sulfur battery according to claim 1, characterized in that: The temperature and time in step (2) are 220° C., 20 h or 240° C., 24 h, respectively.
4. The method for preparing the positive electrode host material of manganese sulfide-molybdenum disulfide heterojunction lithium-sulfur battery according to claim 1, characterized in that: In step (4), the weight ratio of the host material of manganese sulfide-molybdenum disulfide powder and sublimated sulfur powder to sulfur is 3:7 or 1:
9.
5. Application of the manganese sulfide-molybdenum disulfide heterojunction lithium-sulfur battery positive electrode host material prepared by the preparation method according to any one of claims 1 to 4, characterized in that: Sulfur / manganese sulfide-molybdenum disulfide and conductive carbon super P are ground and mixed, and then 5wt% PVDF binder and an appropriate amount of NMP solution are added to form a uniform and fluid slurry with a solid content of 30-40%. The specific amount of NMP used is adjusted according to the total mass of the slurry solids and the corresponding solid content ratio. The solid content ratios corresponding to the slurry adjustment of different materials are slightly different; the mass ratio of sulfur / manganese sulfide-molybdenum disulfide: super P: PVDF is 7:2:1 or 8:1:
1. Finally, the formed uniform and fluid slurry is placed on aluminum foil and scraped with a scraper to form a uniform coating. The coating is dried at 60°C in a vacuum drying oven for 24 hours, cut into discs, weighed, and then assembled into button batteries.
6. Application of the manganese sulfide-molybdenum disulfide heterojunction lithium-sulfur battery positive electrode host material prepared by the preparation method according to any one of claims 1 to 4, characterized in that: In a dry room, soft-pack cells were assembled by stacking, and the area of the coated sulfur / manganese sulfide-molybdenum disulfide working electrode was 24.1 cm 2 , the lithium foil area is 26.1cm 2 , use a vacuum packaging machine to seal the aluminum-plastic film.